Productivity potential of maize hybrids developed at the P.P. Lukyanenko National Grain Center for deep grain processing - V. G. Goldshtein; A. I. Suprunov; P. M. Bogdan; V. V. Sherstobitov; V. I. Khoreva; L. P. Nosovskaya; L. V. Adikaeva; E. B. Khatefov (Труды по прикладной ботанике, генетике и селекции)
Background. The technology of deep grain processing is based on the use of operations that ensure separation of raw materials into various components and sequential processing of these components into products of high consumer value. The annual volume of deep grain processing products is over 100 million tons. Starch, as the most valuable component of processed grain, is used in the food industry, pharmacy, and in significant amounts for technical purposes. Studying the potential of domestic maize hybrids to provide raw materials for deep grain processing enterprises is a relevant task.Materials and methods. The material for field and laboratory studies included 17 commercial maize hybrids developed at the P.P. Lukyanenko National Grain Center. The content of starch, protein and oil in grain was measured with infrared spectroscopy on an Infratec 1241 Grain Analyzer. Actual extraction of native starch was implemented using the “plant-on-the-table” method developed at the All-Russian Research Institute of Starch Products, and breeding trials of maize hybrids were carried out in the steppe zone of Kabardino-Balkaria in 2020/2021.Results. As a result of the research, 13 hybrids with a mass fraction of starch in the range of 70.0–73.2% DM were identified: KR210MV, KR270MV, KR377AMV, KR385MV, KR415MV, ROSS198MV, KR433MV, KR514MV, KR575MV, LYUDMILA, ROSS190MV, and ROSS195MV. Of these, the grain yield in the range of 10–14 t/ha was shown by the hybrids KR270MV, KR315MV, KR377AMV, KR415MV, KR514MV, and KR575MV. In accordance with the results obtained, a number of hybrids can be recommended as source material for breeding and promising raw material for deep grain processing: KR415MV, KR393MV, and ROSS198MV, yielding 90.0–94.4% DW of starch when processed, and KR315MV, with a mass fraction of amylose in starch up to 38.6% DW.